A review of hemostatic chemical components and their mechanisms in traditional Chinese medicine and ethnic medicine. (10th May 2023) - Mu, Kailang; Liu, Yuchen; Liu, Gang; Ran, Fei; Zhou, Lingli; Wu, Yutong; Peng, Leqiang; Shao, Minghui; Li, Changju; Zhang, Yongping
Abstract: Ethnopharmacological relevance: Traditional Chinese medicine and ethnic medicine together play an important value in the modern medicine system that is different from that of chemical drugs. Chinese medicine and ethnic medicine with hemostatic effect have unique advantages and development potential in the prevention and treatment of clinical hemorrhagic diseases, reflecting multi-component, multi-target and multi-pathway effects. Aim of the study: In this paper, the active ingredients related to the hemostatic effect of traditional Chinese medicine and ethnic medicine are taken as the starting point, and the traditional Chinese medicine and ethnic medicine with traditional hemostatic purposes are reviewed, and the existing research progress on the active ingredients and their mechanism of action of these drugs is systematically expounded, aiming to provide theoretical reference for the development of traditional hemostatic drugs, the discovery of hemostatic active ingredients and the research of new hemostatic methods. Materials and methods: Hemostatic chinese medicine and ethnic medicine were collected and summarized from the classic books of Materia Medica, public literature database and doctoral or master's thesis repositories. At the same time, we discussed the classification of various types of hemostatic active ingredients of traditional Chinese medicine and ethnic medicine according to the different mechanisms of hemostasis. Results: A total of 436 traditional Chinese medicine and ethnic medicine with hemostatic effects have been collected, and their hemostatic active ingredients include alkaloids, quinones, flavonoids, phenylpropanoids, organic acids, amino acids, terpenoids, steroids, phenols, tannins, esters, polysaccharides and herbal extracts, etc. These active ingredients accelerate the formation of hemostasis by improving endogenous and exogenous hemostatic pathways mainly through enhancing vascular wall contraction, increasing platelet aggregation, promoting coagulation system activation and inhibiting fibrinolysis. Conclusions: This article reviews the previous data on various aspects of the hemostatic effect of traditional Chinese medicine and ethnomedicine. Many traditional hemostatic drugs have been discovered and many active ingredients and mechanisms have been reported. However, although there are a large number of drugs with traditional hemostatic effects, there are still few developed and applied. At the same time, the hemostatic components of many drugs still remain in the study of the activity of their total extracts, and the potential link between some drug components achieving hemostatic effects through different mechanisms remains to be elucidated. Graphical abstract: Image 1 Highlights: A total of 436 traditional Chinese medicine and ethnic medicine with hemostatic effects have been collected. The hemostatic active ingredients include alkaloids, quinones, flavonoids, phenylpropanol and other chemical components. These active ingredients accelerate the formation of hemostasis mainly through four different pathways. In this paper, many data of traditional drugs for hemostasis and provides a reference for the development of new drugs and methods for hemostasis.